Phytoremediation in Removing Selected Heavy Metals from Aqueous Solutions - Ibrahim, F.H. (Mesopotamian Journal of Marine Sciences, 2021)
Bioaccumulation of Ulothrix zonate was compared for cadmium, copper, nickel, and zinc removal at various concentrations and contact time. The results of the present investigation showed that the lowest amount of Cd, Cu, Ni and Zn was adsorbed when the initial heavy metal concentration was 10 ppm whereas Cd showed highest concentration at 20 ppm and Cu exhibited greatest removal at 30 ppm. The metals Ni and Zn exhibited highest removal at 40 ppm. The value of Freundlich model constant (1/n) for different metals ranged from 0.334 to 0.721 and the values of Langmuir separation factor values (RL) varied between 0.111 and 0.722 which indicated favorable bio-sorption by the biomass of the algae. The order of metals uptake was found to be Ni>Zn>Cu>Cd. The finding of the study showed that U. zonate has much potential as a biosorbent for the sorption of Cd, Cu, Ni and Zn and indicated that the metal uptake was concentration-independent for Cd and Zn whereas for Cu and Ni an increase in initial metal concentration resulted in higher metal uptake. This present study leads the way for the future studies on the use of algae as a cheap bio-adsorbent for heavy metals removal in Iraq which is suffering from huge inland waste water.